Pengaruh Insentif dan Lingkungan Kerja terhadap Kinerja Karyawan Pada PT. Jakarta Laras Citra Tangerang Selatan - Hasna Nur Salsabila; Seno Sudarmono (Jurnal Nusantara Berbakti, 2023)
Jakarta Laras Citra Tangerang Selatan is a company engaged in the field of accounting services and oversees non-formal Japanese-language educational institutions. Quantitative approach method. The population of 40 people is determined by a saturated sample. Data collection techniques using the method of observation, interviews, questionnaires with SPSS Version 25. The results of this study indicate incentives (X1) and work environment (X2) have an effect on employee performance at PT. Jakarta Laras Citra South Tangerang, incentives (X1) are proven from the value of t count > t table (2.653 > 2.026) probability 0.012. The work environment (X2) is proven by the value of t count > t table (2.489 > 2.026) probability 0.017. Simultaneously the two variables affect employee performance, as evidenced by the F test obtained F count > F table (21.061 > 3.24) probability 0.000.